Urban airborne particulate matter origin, chemistry, fate and health impacts - Zereini, Fathi 1949-; Wiseman, Clare L. S. (Environmental science and engineering, environmental engineering, 2011)
This book presents the most up-to-date research and information regarding the origin, chemistry, fate and health impacts of airborne particulate matter in urban areas, a topic which has received a great deal of attention in recent years due to documented relationships between exposure and health effects such as asthma. With internationally recognised researchers and academics presenting their work and key concepts and approaches from a variety of disciplines, including environmental and analytical chemistry, biology, toxicology, mineralogy and the geosciences, this book addresses the topic of urban airborne particulate matter in a comprehensive, multidisciplinary manner. Topics and research addressed in the book range from common methodological approaches used to sample and analyse the composition of airborne particulates to our knowledge regarding their potential to impact human health and the various policy approaches taken internationally to regulate particulate matter levels.